1994
DOI: 10.1515/revneuro.1994.5.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Connectivity: Neural Systems in the Cerebral Cortex

Abstract: The mammalian cerebral cortex is composed of many distinct areas, which are very richly interconnected. The very large number of connections between cortical areas require analysis to be undertaken before reliable conclusions about the organization of neural systems in the cortex can be drawn. We review the methodology and results of two means of analysing central nervous connectivity, hierarchical analysis and optimization analysis. We conclude that these methods are reliable methods for analysing neural conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
108
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(112 citation statements)
references
References 47 publications
3
108
0
1
Order By: Relevance
“…Compared to the experimentally derived binary model, the grading of connection strengths produced a far better performance. In contrast, Young et al (1994) found that graded and binary connectivity matrices produced similar con¢gurations in their structural analyses. However, the similar shape of the error curves across the 14 experiments (¢gure 2) con¢rmed that the two models were quite di¡erent as regards accounting for activity spread.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Compared to the experimentally derived binary model, the grading of connection strengths produced a far better performance. In contrast, Young et al (1994) found that graded and binary connectivity matrices produced similar con¢gurations in their structural analyses. However, the similar shape of the error curves across the 14 experiments (¢gure 2) con¢rmed that the two models were quite di¡erent as regards accounting for activity spread.…”
Section: Discussionmentioning
confidence: 89%
“…As with other neuroinformatic studies (e.g. Hilgetag et al 1996;Jouve et al 1998;Young 1993;Young et al 1994) we could prepare a list indicating what coupling strength presently unknown pathways should have in order to minimize the mismatch, suggesting further experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, aside from its connections with the limbic system [7] , the vMPFC is connected to the DLPFC [94] which is important for working memory performance and the temporal organization of behavior [90,95] . The DLPFC exerts executive control on the vMPFC, through which the limbic system is affected in turn [96] , which might explain the vMPFC-MTL/PHC/amygdala dysconnectivity observed in the present study.…”
Section: Alteration Of Vmpfc Rsfc In Schizophreniamentioning
confidence: 99%
“…Anatomically, the ventral MFC (vMFC) is the lower part of the frontal cortices and consists of the rostral and subcallosal parts of the anterior cingulate gyrus, the medial portion of the orbitofrontal cortex, and the area in between [6] ; it is intimately connected to the limbic system [7,8] . It is critical to the integration of emotion and cognition by the use of so-called "somatic markers" [9,10] .…”
mentioning
confidence: 99%
“…Every major sensory system in the cat and monkey cortex, and the gross cortical organization of each animal, were analyzed in this way (Scannell and Young 1993;Young 1992;1993;Young et al, 1994aYoung et al, , 1994bScannell et al 1995;Young et al, 1995). In this approach, connection data are considered to indicate the proximities between brain structures in a high-dimensional "connection space", and NMDS is us-d to reduce the number of dimensions of the space to make the configuration defined by the connections more understandable.…”
mentioning
confidence: 99%